Pengembangan Potensi Desa Wisata di Banyumas Menuju Pembangunan Perdesaan Berkelanjutan - Agung Kurniawan; Tyas Retno Wulan; Muslihudin Muslihudin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Sustainable Development Goals or sustainable development is a development concept carried out by the government to improve the community's welfare and preserve the environment. The national development program is now starting to experience a paradigm shift. Previously, the focus of development was more emphasized on the economic sector in local government areas only, but now the director of development is starting to target rural areas as the most significant contributor to achieving the success of national development. The purpose of this research is to map tourist villages in Banyumas Regency into several categories according to their potential and level of development. This research was conducted from October to November 2022 with the selection of research locations carried out purposively based on considerations of being a village that has a tourist location, both developed and newly developed, having various village potentials such as nature, culture, and UMKM, managed by the village government and residents supported by the local government, universities, and investors spread across 13 tourist villages in the Banyumas Regency area Kalisalak, Wlahar Wetan, Linggasari, Melung, Papringan, Pandak, Banjaranyar, Limpakuwus, Kalisari, Susukan, Karangsalam Lor, Cikakak, and Karang Tengah. The population in this study amounted to 160 people, with a research sample of 90 people consisting of 14 village governments, 48 tourism managers, and 28 local villagers. This research uses qualitative data analysis methods with primary data sources obtained directly from the field and supported by secondary data obtained by researchers from various media such as the Internet and other research results as support. The data collection techniques used in this research were structured interviews, observation, and literature study. The results showed that several village areas in Banyumas Regency have become tourist villages or pioneered to become tourist villages with a management system carried out by the local community in collaboration with the village government and in partnership with external parties such as universities, investors, and local governments. These villages have various characteristics of potential that can be developed, such as natural potential, artistic potential, and UMKM. Seen from the level of development, tourist villages in Banyumas Regency are divided into several categories, namely the tourist village category, the developing tourist village category, and the embryonic village category.